2022
DOI: 10.1096/fj.202101610r
|View full text |Cite
|
Sign up to set email alerts
|

Activation of osteoblast ferroptosis via the METTL3/ASK1‐p38 signaling pathway in high glucose and high fat (HGHF)‐induced diabetic bone loss

Abstract: Diabetes mellitus (DM) and osteoporosis are two common diseases that may develop as a cause-and-effect relationship since the incidence of osteoporotic fractures is significantly increased in DM patients. However, the pathophysiology of diabetic osteoporosis is yet to be clearly understood. Iron overload has been reported to lead to bone loss and closely related to osteoporosis. In this study, we hypothesized that high glucose and high fat (HGHF) may induce osteoblastic ferroptosis for the pathogenesis of diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 56 publications
4
43
0
Order By: Relevance
“…Ma et al found that the m 6 A reader YTHDC2 promotes SLC7A11 mRNA decay by binding to m 6 A-modified SLC7A11 mRNA [32]. Consistent with our results, Lin et al also showed that knockout of METTL3 in pre-osteoblastic MC3T3-E1 cells attenuated the level of ferroptosis [44]. However, Xu et al revealed that METTL3-mediated m 6 A modification of SLC7A11 mRNA was read by YTHDF1, which promoted the translation of SLC7A11 mRNA to inhibit lung adenocarcinoma cell ferroptosis [45].…”
Section: Discussionsupporting
confidence: 91%
“…Ma et al found that the m 6 A reader YTHDC2 promotes SLC7A11 mRNA decay by binding to m 6 A-modified SLC7A11 mRNA [32]. Consistent with our results, Lin et al also showed that knockout of METTL3 in pre-osteoblastic MC3T3-E1 cells attenuated the level of ferroptosis [44]. However, Xu et al revealed that METTL3-mediated m 6 A modification of SLC7A11 mRNA was read by YTHDF1, which promoted the translation of SLC7A11 mRNA to inhibit lung adenocarcinoma cell ferroptosis [45].…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have shown that Fer-1 and DFO block ferroptosis induced by HG and palmitic acid (HGPA) in MC3T3-E1 cells. The mechanism of high glucose and high fat (HGHF)-induced ferroptosis in osteoblasts is related to the activation of the METTL3/ASK1-p38 signaling pathway ( 114 ). Morphological changes of mitochondrial are the important hallmark of ferroptosis, and studies have shown that mitochondria play an important role in the regulation of ferroptosis via regulation of energetic metabolism, iron metabolism, and other pathways ( 115 , 116 ).…”
Section: Effects and The Molecular Mechanisms Of Ferroptosis On Diabe...mentioning
confidence: 99%
“…Furthermore, the relationship between ferroptosis and glucocorticoid-induced osteoporosis (GIOP) has been well investigated [ 62 ]. For example, a recent study [ 47 ] reported that high-dose dexamethasone (10 μ M) can induce ferroptosis of OB by inhibiting the expression of GPX4 and system Xc − .…”
Section: Ferroptosis and Bone Degenerative Disordersmentioning
confidence: 99%
“…Mechanistically, activation of Nrf2/HO-1 signaling could lead to lipid peroxidation and cell ferroptosis, suggesting that targeting inhibition of OCT ferroptosis may be a potential therapeutic strategy for DOP treatment [53]. Furthermore, the relationship between ferroptosis and glucocorticoid-induced osteoporosis (GIOP) has been well investigated [62]. For example, a recent study [47] reported that high-dose dexamethasone (10 μM) can induce ferroptosis of OB by inhibiting the expression of GPX4 and system Xc -.…”
Section: Ferroptosis and Osteoporosismentioning
confidence: 99%